2004
DOI: 10.1002/elan.200302954
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Au Electrodes Based on SAMs of per(6‐deoxy‐6‐thio‐2,3‐di‐O‐methyl)‐β‐cyclodextrin

Abstract: A three-step sequential self-assembly procedure was applied in preparing gold electrodes modified in a stable and controlled way by a monolayer of thiolated b-cyclodextrin (b-CD), with methylene blue (MB) included in its cavity as the active component of the monolayer, and octanethiol as the nonelectroactive spacer blocking the electrode surface not occupied by b-CD. MB acted as a mediator of electrons with respect to a solution soluble analyte, H 2 O 2 , and provided electrical contact between the electrode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Octanothiol was used to seal the remaining empty space, done despite the fact that it reduces the efficiency of the ET process. This modified gold electrode was used to self-assemble laccase with methylene blue included in the CD cavities as a mediator . A similar approach was also applied but without sealing the empty surface of the gold electrode and using a modified enzyme.…”
Section: 1 Electrochemical Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Octanothiol was used to seal the remaining empty space, done despite the fact that it reduces the efficiency of the ET process. This modified gold electrode was used to self-assemble laccase with methylene blue included in the CD cavities as a mediator . A similar approach was also applied but without sealing the empty surface of the gold electrode and using a modified enzyme.…”
Section: 1 Electrochemical Biosensorsmentioning
confidence: 99%
“…This modified gold electrode was used to selfassemble laccase with methylene blue included in the CD cavities as a mediator. 242 A similar approach was also applied but without sealing the empty surface of the gold electrode and using a modified enzyme. In this report the authors did not discuss the stability of the biosensor.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Other work 225 also showed the response of these types of monolayer to a variety of substrates and further demonstrated that mixed monolayers of the cyclodextrins with simple alkyl thiols were of higher quality than films of cyclodextrin alone. 227 Similar work on various quinine mediators in solution has shown that electron transfer only occurs when the mediator is of a size that allows it to enter the cyclodextrin cavity. 226 This process could be affected by the presence of a naphthalene guest in the cyclodextrin cavity.…”
Section: Conclusion 243mentioning
confidence: 94%
“…The monolayers are usually well packed, ordered, and stable and can be easily tailored for certain applications by changing the functional terminal group in contact with the solution. Alkanethiol monolayers can provide a membrane matrix useful for immobilizing structures such as cylodextrins [80][81][82].…”
Section: Self-assembly Methodsmentioning
confidence: 99%